The use of cloud technologies in universities. Google services - V. M. Franchuk (Academy of Cognitive and Natural Sciences, 2013)
Google is a mathematical term for 1 with 100 zeros. The term was introduced by Milton Sirota, nephew of the American mathematician Edward Kasner, and described in Kasner and James Newman's book Mathematics and Imagination. Google's play on words reflects the company's mission, which is to organize the vast amount of data available on the global Internet. Google's work is based on a single goal: to organize the data accumulated around the world and make it as accessible and useful as possible. An important aspect in accomplishing this challenging task is to organize the knowledge base held by academic institutions. In an academic environment, data sharing is essential for both teaching and research. In this regard, Google provides tools to improve knowledge sharing and collaboration that students, faculty, and other community members can use anytime, anywhere.